A toolkit to implement graduate attributes in geography curricula. Issue 2 (2nd April 2016) - Spronken-Smith, Rachel; McLean, Angela; Smith, Nell; Bond, Carol; Jenkins, Martin; Marshall, Stephen; Frielick, Stanley
Abstract: This article uses findings from a project on engagement with graduate outcomes across higher education institutions in New Zealand to produce a toolkit for implementing graduate attributes in geography curricula. Key facets include strong leadership; academic developers to facilitate conversations about graduate attributes and teaching towards them; ownership of the process by the teachers; the development of a contextualized set of graduate attributes for the geography degree; curriculum mapping to promote alignment between graduate attributes, learning outcomes and assessment tasks; incorporating high-impact educational experiences and signature pedagogies to foster graduate attributes; the use of evaluative data to inform continual enhancements; and allowing at least five years for curriculum renewal to occur.